ANSWERING ASSUMPTIONS REGARDING THE INCONSISTENCY OF 'AWDUDH-DHOMIR IN THE QUR'AN - Sajidan Insi (RADJA PUBLIKA, 2026)
The accusations attached to the Qur'an has happened even since the time of the Prophet Muhammad SAW, and Allah challenged for anyone to make​ letter such as those in the Koran. In this day and age of accusations against the Qur'an is done through orientalism . The colonizers attack Islam in a way confidential through orientalist . One of the the target is eradicate Arabic and revoke it from people Islam . One of the branch indicated science​ existence accusations by orientalists is knowledge syntax ( nahw ), more especially in the chapter ' awdudh- dhomīr claimed happen inaccuracy in return dhomīr his to the previous word . This is become reason they For weaken the Qur'an in the heart people Muslims and also for accuse that the Qur'an is a holy book that is not ma'shūm( awake) from error ). Because of that that , in this article will analyze as well as answer assumptions about mismatch ' awdudh-dhomīr in the Qur'an.